The Connection between Pregnancy Spacing and the Occurrence of Stunting in Children : An In-Depth Analysis of Contributing Factors - Hetty Johana Sulung; Rifzul Maulina; Anik Sri Purwanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Stunting is a serious nutritional problem in Indonesia, affecting the growth and development of children under five years of age. Non-ideal pregnancy spacing is one of the factors that can contribute to stunting, as closely spaced pregnancies can lead to inadequate maternal nutrition, which affects the child’s development. This study aims to analyze the relationship between pregnancy spacing and the incidence of stunting in children under five. The research design employed is observational analytic with a case-control approach. Data collection was conducted from February to October 2024, focusing on children with stunting and children with normal growth as control cases. The case-control study involved a total sample size of 60 children, with 30 stunted children as cases and 30 non-stunted children as controls. The control cases were selected using simple random sampling to ensure unbiased representation. The primary analysis technique used was the chi-square test to examine the relationship between pregnancy spacing and the incidence of stunting. The results indicated that children born with a pregnancy spacing of less than 24 months had a 1.5 times higher risk of experiencing stunting compared to those born with a pregnancy spacing of more than 24 months. Statistical analysis using the chi-square test yielded a significant p-value of 0.002 (< 0.05), which confirms a strong association between short pregnancy spacing and stunting. This study concludes that insufficient pregnancy spacing is a significant factor contributing to the incidence of stunting in children under five. Therefore, it is recommended that public health campaigns and education programs on family planning and reproductive health be strengthened to reduce the risk of stunting in Indonesia. Such initiatives will help prevent future generations from experiencing the negative effects of inadequate growth and development.